Legal Politics of Holding the 2024 Elections the Absolute and Ideal and Constitutional - Muhammad Zulhidayat; Rosi Mirnawati; Amina Intes; Uwe Barroso; Elladdadi Mark (Yayasan Adra Karima Hubbi, 2023)
Background. The holding of simultaneous elections on April 17 2019 is a new history in the general election process in Indonesia. This is an implication of the Constitutional Court Decision Number 14/PUU/2013 in the case of reviewing Law Number 42 of 2008 concerning the General Election of the President and Vice President. Even though the simultaneous elections have been judged to be better than the previous elections, it does not mean that they do not have deficiencies in their implementation. Purpose. The most shocking problem was the large number of fatalities by election organizers which were considered to be the impact of the 2019 simultaneous election and other technical problems. Method. Looking at the various sides that emerged from the 2019 elections, the Association for Elections and Democracy (Perludem) conducted a judicial review of the 1945 Constitution to the Constitutional Court as outlined in the Constitutional Court Decision Number 55/PUU-XVII/2019. Results. In his argument, the applicant conveyed a number of things related to the analysis that had been carried out in the implementation of the simultaneous elections which were held in 2019 yesterday. In the results of this decision, the Constitutional Court reject the applicant's application in its entirety because it is considered that the application has no legal grounds. Conclusion. However, the Constitutional Court provided options related to simultaneous election models that can be selected and considered constitutional based on the 1945 Constitution.